Postnatal height and adiposity gain, childhood blood pressure and prehypertension risk in an Asian birth cohort - Aris, Izzuddin M (Int J Obes (Lond), 2017)
OBJECTIVE: There have been hypotheses that early life adiposity gain may influence blood pressure (BP) later in life. We examined associations between timing of height, body mass index (BMI) and adiposity gains in early life with BP at 48 months in an Asian pregnancy-birth cohort. METHODS: In 719 children, velocities for height, BMI and abdominal circumference (AC) were calculated at five intervals [0-3, 3-12, 12-24, 24-36 and 36-48 months]. Triceps (TS) and subscapular skinfold (SS) velocities were calculated between 0-18, 18-36 and 36-48 months. Systolic (SBP) and diastolic blood pressure (DBP) was measured at 48 months. Growth velocities at later periods were adjusted for growth velocities in preceding intervals as well as measurements at birth. RESULTS: After adjusting for confounders and child height at BP measurement, each unit z-score gain in BMI, AC, TS and SS velocities at 36-48 months were associated with 2.3 (95% CI:1.6, 3.1), 2.1 (1.3, 2.8), 1.4 (0.6, 2.2) and 1.8 (1.0, 2.6) mmHg higher SBP respectively, and 0.9 (0.4, 1.4), 0.9 (0.4, 1.3), 0.6 (0.1, 1.1) and 0.8 (0.3, 1.3) mmHg higher DBP respectively. BMI and adiposity velocities (AC, TS or SS) at various intervals in the first 36 months however, were not associated with BP. Faster BMI, AC, TS and SS velocities, but not height, at 36-48 months were associated with 0.22 (0.15, 0.29), 0.17 (0.10, 0.24), 0.11 (0.04, 0.19) and 0.15 (0.08, 0.23) units higher SBP z-score respectively, and OR=1.46 (95% CI: 1.13-1.90), 1.49 (1.17-1.92), 1.45 (1.09-1.92) and 1.43 (1.09, 1.88) times higher risk of prehypertension/hypertension respectively at 48 months. CONCLUSION: Our results indicated that faster BMI and adiposity (AC, TS or SS) velocities only at the preceding interval before 48 months (36-48 months), but not at earlier intervals in the first 36 months, are predictive of BP and prehypertension/hypertension at 48 months.